Investigating magnetic fields for pharmaceutical processing - Bratty, Victoria Louise (2020)
Many pharmaceutical compounds have poor aqueous solubilities that can result in difficulties in formulation, and ineffective therapeutic treatments. Pharmaceutical compounds can exist in different states (i.e. amorphous or crystalline), as well as existing in different polymorphic forms, which can dramatically affect physicochemical properties. However, a technique called containerless processing has shown promise in the control of crystallisation and crystal form. Using high strength magnetic fields (> 16 T) that are strong enough to freely levitate pharmaceutical solutions we investigated the potential of magnetic levitation for containerless processing.